Optimal Control Strategies for Coffee Berry Disease with Cost-Effectiveness Analysis in the Presence of Climatic Variability - Melese, Abdisa Shiferaw; Makinde, Oluwole Daniel; Obsu, Legesse Lemecha (Journal of Applied Nonlinear Dynamics, 2026)
This paper aims to tackle an important problem - the optimization of measures applied to fight disease in one of the most important economically plant cultures: coffee. This is done by formulating a mathematical model of coffee berry disease (Colletotrichum kahawae) with optimal controls which consist of coffee berry and vector population with the interaction of pathogen, temperature variability, and rainfall pattern. First, we investigate the positivity and boundedness of solutions of the proposed model with the absence of controls. Then, optimal control strategies are studied to minimize the burden of coffee berry disease (CBD) and the cost of interventions. The characterization of optimal trajectories is also analytically derived using Pontryagin's Minimum Principle. Finally, we performed numerical simulations to investigate the impact of control strategies in combating CBD. Furthermore, we studied the cost-effectiveness of our control strategies to determine the best approach to minimize the disease burden. The finding of this study shows that any combination of genetic resistance variety, chemical and cultural control strategies are very effective to combat the disease.